Correlation of Renal Scarring to Urinary Tract Infections and Vesicoureteral Reflux in Children - Hamdy Aboutaleb; Tamer A. Abouelgreed; Hala El-Hagrasi; Diaa Bakry Eldib; Mohamed A. Abdelaal; Mohamed Amin El Gohary (Advances in Urology)
Objective. To study the association of the grade of vesicoureteral reflux (VUR) and urinary tract infections (UTI) with renal scarring at the first clinical presentation of patients who underwent antireflux surgery. Materials and methods. Between 2015 and 2020, 150 patients (194 units) who underwent antireflux surgery had dimercaptosuccinic acid (DMSA) renal scans preoperatively. Patients were classified into the nonscar and scar groups according to DMSA scan results. Moreover, cases were classified into afebrile UTI, febrile UTI, and antenatal hydronephrosis (ANH) according to the mode of presentation. We correlated the mode of presentation and the grade of VUR to the presence/absence of renal scars in both groups. Results. The mean follow-up was 45 months preoperatively. The mode of presentation was afebrile, febrile UTIs, and antenatal hydronephrosis in (50, 14), (20, 46), and (10, 10) patients in the nonscar and scar groups, respectively. Of the 20 patients who presented ANH, 10 (50%) had scars. Clinical presentation was correlated to the presence of renal scarring and its degree. The scar group had significantly higher grades of VUR than the nonscar group (grades I–II (50 units versus 10 units), grade III (28 units versus 40 units), and grade IV–V (22 units versus 44 units) for the nonscar versus scar groups, respectively (pvalue <0.001). Conclusion. Renal scarring is associated with higher grades of reflux and urinary tract infections. We advocate further research investigating infants who had UTIs with or without fever for early detection of reflux.